The Strategy of Madrasah Headmaster in Improving The Quality of Islamic Education - Sakinah Sakinah; Asy’ari Asy’ari; Moh. Ali (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2019)
This study examines the strategies of madrasa headmasters in improving the quality of Islamic Education and the facilitating and hindering factors as well as the solutions of the headmaster's strategies in improving the quality of Islamic Education in Madrasah Tsanawiyah. This study used descriptive qualitative and research design using a case study approach. The data were collected using observation, interview, and documentation techniques. Data analysis techniques through data reduction analysis, data presentation, and data verification which ended with checking the validity of the data. The results showed that: 1) The strategy employed by the madrasah headmaster in improving the quality of Islamic Education begins with an analysis of the internal and external environment of the madrasa which includes strengths and weaknesses, as well as the threats and opportunities. Head of Madrasah TsanawiyahAlkhairaatSibalaya always builds harmony in the organization, for example, being able to place personnel appropriately and influence his subordinates in human relationships which are covered by authority situations, enforce discipline to all madrasa personnel, and empower teachers to improve their competency and evaluate by involving relevant and professional related parties.2) The supporting factors are harmonious cooperation with subordinates as well as the conducive and comfortable situation and conditions of the madrasa. Meanwhile, inhibiting factors are the lack of teachers' discipline and lack of community response to send their children to madrasas.